Are Young Mothers in India Deprived of Maternal Health Care Services? A Comparative Study of Urban and Rural Areas. (June 2015) - Kavitha, N.
This article attempts to study the effect of age of women at birth on the use of maternal health care services separately for urban and rural areas using data from the National Family Health Survey (NFHS)-3, 2005–2006, India. The indicators of use of maternal health care services used in this study are use of antenatal care services recommended by the World Health Organization (WHO) (includes three or more antenatal check-ups during the first trimester, two or more tetanus toxoid (TT) injections and taking 100 iron and folic acid tablets during pregnancy), place of delivery, assistance at delivery and use of postnatal care services. At first, the percentage of births that utilized various maternal health care services are discussed separately for urban and rural areas, followed by difference in utilization of maternal health care services between adolescent and adult mothers. Finally, logistic and multinomial regressions are used to examine the influence of age of women at birth on the use of maternal health care services for controlling for other factors. Multivariate results revealed that women who gave birth during adolescence are less likely to use antenatal, natal and postnatal care services in both urban and rural areas. Therefore, efforts should be made to educate parents and other family members on the consequences of early marriage and early pregnancy and also the importance of delaying marriage.